Strategic Commitment by Sultanate of Oman towards 2050 Net-Zero Emission: Current Environmental Initiatives and Future Needs - Alrawahi I.; Bathmanathan V.A.P.; Al Kaabi S.; Alghalebi S. (Cosmos Scholars Publishing House, 2024)
Global warming is a major concern to humanity due to its massive environmental impact. Studies emphasize low-carbon issues such as emissions policy, carbon taxation, carbon emissions trading, and emissions accounting and reduction (Gao et al., 2014). This paper will cover one of the main commitments towards environmental protection, which is 2050 net zero emissions. Many countries have set this target to show a clear commitment to reducing their CO2 and other greenhouse gases (GHGs) to zero in the coming 30 years. Yet the main question here would these targets be aspirational or realistic? If the goals are aspirational, does this encourage more effort, or will it make the public and investors even more critical of the government if they fail? How does the mission to maintain average temperature increases below 2C or, preferably, 1.5C by 2100 relate to the net zero by 2050 goal? In October 2022, Oman joined the current effort to protect the environment and reach net zero by 2050. The country has already implemented many environmental measures